Integrating Public Deliberation into Engineering Systems: Participatory Technology Assessment of NASA's Asteroid Redirect Mission. Issue 2 (4th May 2017) - Tomblin, David; Pirtle, Zachary; Farooque, Mahmud; Sittenfeld, David; Mahoney, Erin; Worthington, Rick; Gano, Gretchen; Gates, Michele; Bennett, Ira; Kessler, Jason; Kaminski, Amy; Lloyd, Jason; et al.
ABSTRACT: We discuss an experiment employing participatory technology assessment (pTA), a public deliberation method for eliciting lay citizen input prior to making decisions about science and technology to inform upstream engineering decisions concerning technical aspects of NASA's Asteroid Initiative. In partnership with NASA, the Expert and Citizen Assessment of Science and Technology network conducted a pTA forum on NASA's Asteroid Initiative in 2014. The goal of the exercise was to assess citizens' values and preferences about potential asteroid detection, asteroid mitigation, and exploration-based technologies associated with NASA's Initiative. This article discusses the portion of the forum that focused on the Asteroid Redirect Mission, an effort to redirect an asteroid into lunar orbit that astronauts can study. The forum sought public input on two options for performing the mission that NASA included in technical assessments to make a down select decision: Option A to capture a 10-meter-diameter asteroid; or Option B to redirect a several-meters-diameter boulder from the surface of a larger asteroid. We describe the values and perceptions participants had about Option A and B, how these results were used by NASA managers, and the impact the results of the pTA had on the down select.